A Numerical computation for solving the fractional delay differential equations via the MQ-RBF collocation method - Aghdam, Yones Esmaeelzade; Safdari, Hamid; Azari, Yaqub; Banee, Siamak (Sulaimani Journal for Pure and Applied Sciences, 2020)
In the paper, a numerical technique based on the multiquadric radial basis function (MQ-RBF) collocation method is presented for the fractional delay differential equations. The convergence analysis and the unique fixed point of the collocation methods are propounded in the norm. Numerical results illustrate the credibility and applicability of the numerical technique. The obtained results are compared with those obtained by other methods.
Keywords: Collocation Scheme; Fractional Calculus; Fixed Point; MQRBF